Nasci aqui e cresci lá: conflitos identitários de jovens brasileiros adotados por pais estrangeiros - ALVES, Ivonita Santos (2014)
This doctoral thesis approaches the identity conflict issue amongst Brazilian juveniles that were adopted by European families in five different countries in Europe from 1980 to 2000. When adopted, they were poor black children completely abandoned by their families and by the Brazilian Nation-State. This study advances studies on that subject-matter by giving a special focus on post adoption and by letting emerge a specific point of view: adopted individuals that are currently black juveniles with interaction and life experience within white adoptive families and social groups in which occurs an auto perception as being the only black individuals on such interaction environment. Although the majority of those individuals have the feeling of been integrated into the countries in which they live in, study and/or work, there is still a demand from their side for knowing the reasons of their adoptions, to know who their biological parents were and if they wish to return or returned in fact to Brazil. As for the theoretical background, the study dialogues, mostly, with references from the social sciences and cultural studies on the attempt of understanding identity conflicts implied on international adoption when considering inter-racial and inter-cultural relationships. The present study analyses numerical data and life history reports from adopted juveniles collected by means of survey research, interviews with juveniles, adoptive parents and friends, as well as, observations and resources from the researcher’s memory. It explains why and how three identity conflicts occur along the study, such as: the juvenile’s relationship with his adoption process and with his adoptive parents; the pertaining feeling and the seeking of his origins and racial discrimination experiences. Results indicate that adoption turns out possible to have a social insertion on the adoptive family and country, but the questionings on the reasons of why they were adopted persisted, as well as, the strong desire of meeting their biological parents and their homeland country. The study also indicates that racial discrimination is commonly faced on groups to which they make part of, specially the school.